Cold Atmospheric Plasma Induces Apoptosis and Oxidative Stress Pathway Regulation in T-Lymphoblastoid Leukemia Cells. (29th August 2017) - Turrini, Eleonora; Laurita, Romolo; Stancampiano, Augusto; Catanzaro, Elena; Calcabrini, Cinzia; Maffei, Francesca; Gherardi, Matteo; Colombo, Vittorio; Fimognari, Carmela
Abstract : Cold atmospheric plasma (CAP) has shown its antitumor activity in both in vitro and in vivo systems. However, the mechanisms at the basis of CAP-cell interaction are not yet completely understood. The aim of this study is to investigate CAP proapoptotic effect and identify some of the molecular mechanisms triggered by CAP in human T-lymphoblastoid leukemia cells. CAP treatment was performed by means of a wand electrode DBD source driven by nanosecond high-voltage pulses under different operating conditions. The biological endpoints were assessed through flow cytometry and real-time PCR. CAP caused apoptosis in Jurkat cells mediated by p53 upregulation. To test the involvement of intrinsic and/or extrinsic pathway, the expression of Bax/Bcl-2 and caspase-8 was analyzed. The activation of caspase-8 and the upregulation of Bax and Bcl-2 were observed. Moreover, CAP treatment increased ROS intracellular level. The situation reverts after a longer time of treatment. This is probably due to compensatory cellular mechanisms such as the posttranscriptional upregulation of SOD1, CAT, and GSR2. According to ROS increase, CAP induced a significant increase in DNA damage at all treatment conditions. In conclusion, our results provide a deeper understanding of CAP potential in the oncological field and pose the basis for the evaluation of its toxicological profile.